Modelling the behavior of I-shape concrete beams reinforced with fibers and prestressed steel and GFRP bars - Shahrbijari, Kamyar Bagherinejad (2023)
This paper reports the behavior of I-shaped fiber reinforced concrete (FRC) beams flexurally reinforced with prestressed steel and glass fiber reinforced polymer (GFRP) bars. The use of steel fibers aims to enhance the durability of pre-fabricated concrete structures by partially or completely replacing steel stirrups. In addition, GFRP and steel bars/tendons are combined as flexural reinforcement, creating a hybrid reinforcement system. GFRP bars are immune to corrosion and are positioned with minimum concrete cover, while steel reinforcement has adequate concrete cover thickness to minimize its risk to corrosion and ensure the required flexural capacity in a fire occurrence. Nonlinear finite element analysis (NLFEA) software was utilized for a critical analysis on the use of smeared crack model for predicting the behavior of this type of beams, including deflection, crack pattern, load-carrying capacity, and failure modes.